High-density magnesia insulation material for ultra-high temperature and preparation method thereof

CN122940441APending Publication Date: 2026-10-20LIAONING JIASHUN CHEM SCI & TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611434002.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种特高温用高密度氧化镁绝缘材料及其制备方法,以解决现有含烧结助剂高密度氧化镁体系在1600℃以上特高温氧化气氛下,高温导电激活导致体积电阻率急剧下降、以及反复热循环后绝缘性能大幅劣化的问题

Benefits of technology

[0027]1.前驱体包覆氧化镁颗粒经溶胶-凝胶法改性后,可在常压烧结条件下实现高致密化,克服了纯氧化镁常压烧结难致密化、需依赖传统含铝硅酸盐类助剂的局限,为材料在1600℃以上特高温氧化气氛下的应用提供了致密化基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

This invention belongs to the technical field of magnesium oxide insulating materials, specifically a high-density magnesium oxide insulating material for ultra-high temperatures and its preparation method. It aims to solve the problems of decreased volume resistivity and deteriorated insulation performance of existing high-density magnesium oxide systems containing sintering aids under ultra-high temperature oxidizing atmospheres above 1600℃. The material is formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination. The former achieves high densification through atmospheric pressure sintering, while the latter improves the volume resistivity at ultra-high temperatures. The combination of the two avoids component segregation, giving the material both high density and ultra-high temperature insulation stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of magnesium oxide insulating materials, specifically a high-density magnesium oxide insulating material for ultra-high temperature applications and its preparation method. Background Technology

[0002] Magnesium oxide has a melting point of 2852℃ and exhibits excellent electrical insulation properties at room temperature, making it an important insulating material for mineral-insulated cables and high-temperature heating elements. However, pure magnesium oxide is a strongly ionic crystal with a low intrinsic diffusion coefficient, making densification by atmospheric pressure sintering difficult. Therefore, sintering aids are usually introduced to activate grain boundary diffusion and promote densification.

[0003] Patent publication number CN118724033A discloses a high-temperature magnesium oxide powder additive, a method for preparing magnesium powder, and its applications. This patent uses kaolin, alumina, and silicon dioxide as the main additive components, and utilizes an aluminosilicate second phase formed at grain boundaries to achieve densification. However, the insulation performance of this aluminosilicate second phase decreases above 600°C, thus limiting its application to conventional heating element conditions at 600°C and below, and failing to meet the insulation requirements under ultra-high temperature oxidizing atmospheres above 1600°C.

[0004] In extreme operating conditions such as aerospace and nuclear industries, equipment like mineral-insulated cables need to operate for extended periods in ultra-high-temperature oxidizing atmospheres exceeding 1600°C, placing extremely stringent requirements on the volume resistivity of insulating materials. Studies show that within this temperature range, the volume resistivity of polycrystalline magnesium oxide containing sintering aids is lower than that of magnesium oxide without aids of the same purity. The fundamental reason is that under ultra-high-temperature oxidizing atmospheres above 1600°C, the activation energy for conductivity in the second phase and defect-rich regions at grain boundaries decreases. Ionic and electronic conduction channels are synergistically opened at high temperatures, forming low-resistance leakage paths that penetrate the grain boundary network, leading to a rapid deterioration in the overall insulation performance of the material at ultra-high temperatures. Summary of the Invention

[0005] (1) Technical problems to be solved

[0006] The purpose of this invention is to provide a high-density magnesium oxide insulating material for ultra-high temperatures and its preparation method, in order to solve the problems of existing high-density magnesium oxide systems containing sintering aids, which suffer from a sharp decrease in volume resistivity due to high-temperature conductivity activation under ultra-high temperature oxidizing atmospheres above 1600℃, and significant deterioration of insulation performance after repeated thermal cycling.

[0007] (2) Technical solution

[0008] To achieve the above objectives, on the one hand, the present invention provides a high-density magnesium oxide insulating material for ultra-high temperature applications, comprising a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; wherein the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:0.5~2.0.

[0009] The precursor-coated magnesium oxide particles are obtained by coating the surface of magnesium oxide powder particles with a precursor gel layer using tetraethyl orthosilicate and tetrabutyl titanate as hydrolyzed precursors via a sol-gel method.

[0010] The precursor-coated titanium dioxide particles are obtained by loading a precursor coating layer onto the surface of anatase titanium dioxide nanoparticles using yttrium nitrate hexahydrate and stannous chloride as coating sources via a co-precipitation method.

[0011] Furthermore, the magnesium oxide powder has a purity of ≥99.9% and a particle size of 1~3μm; the anatase titanium dioxide nanoparticles have a purity of ≥99% and a particle size of ≤100nm.

[0012] Furthermore, the preparation method of the precursor-coated magnesium oxide particles includes the following steps:

[0013] M11. Under stirring, tetraethyl orthosilicate was dissolved in anhydrous ethanol-water mixed solvent, and dilute nitric acid was added dropwise to adjust the pH. Hydrolysis was then performed to obtain a precursor sol. Separately, tetrabutyl titanate was dissolved in anhydrous ethanol, and acetylacetone was added and stirred to obtain a precursor solution.

[0014] M12. Add the precursor solution to the silicon precursor sol with stirring. Continue stirring after the addition is complete to obtain a composite precursor sol. Add dilute ammonia solution to the composite precursor sol to adjust the pH. Then add high-purity magnesium oxide powder, sonicate, and stir to react to obtain a reaction mixture.

[0015] M13. Vacuum dry the reaction mixture to obtain a dry powder; grind and sieve the dry powder to obtain precursor-coated magnesium oxide particles.

[0016] Further, the mass ratio of tetraethyl orthosilicate to tetrabutyl titanate is 1:0.2~0.4; the mass ratio of acetylacetone to tetrabutyl titanate is 1:3~1:4; and the mass ratio of high-purity magnesium oxide powder to the total mass of tetraethyl orthosilicate and tetrabutyl titanate is 5:1~10:1.

[0017] Furthermore, the preparation method of the precursor-coated titanium dioxide particles includes the following steps:

[0018] M21. Add anatase titanium dioxide nanoparticles to deionized water and sonicate to obtain a titanium dioxide suspension; dissolve yttrium nitrate hexahydrate in deionized water to obtain a yttrium nitrate hexahydrate solution; dissolve stannous chloride in deionized water and add 1 mol / L hydrochloric acid dropwise, stir and mix with the yttrium nitrate hexahydrate solution to obtain a mixed solution;

[0019] M22. Add the mixed solution to the titanium dioxide suspension; after the addition is complete, stir the reaction; then add 2 mol / L ammonia solution to adjust the pH of the system; continue stirring and aging to obtain a suspension;

[0020] M23. Filter the suspension and wash it with deionized water; dry the washed filter cake, grind it lightly and sieve it to obtain precursor-coated titanium dioxide particles.

[0021] Furthermore, the amount of yttrium nitrate hexahydrate added is 0.5-1% of the mass of anatase titanium dioxide nanoparticles; the amount of stannous chloride added is 0.3-0.8% of the mass of anatase titanium dioxide nanoparticles.

[0022] Furthermore, the preparation method of the high-density magnesium oxide insulating material for ultra-high temperature applications includes the following steps:

[0023] M1. Precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles are co-dispersed in an ethanol-water mixed solvent, dilute hydrochloric acid is added dropwise to adjust the pH of the system, and the reaction is stirred to obtain a composite precursor slurry.

[0024] M2. The composite precursor slurry is dried to obtain a dry powder; the dry powder is ground and sieved; the sieved powder is calcined in an oxidizing atmosphere; after cooling, it is taken out, ground, and sieved to obtain a high-density magnesium oxide insulating material for ultra-high temperature applications.

[0025] Furthermore, the total mass ratio of the precursor-coated magnesium oxide particles and the precursor-coated titanium dioxide particles to the ethanol-water mixed solvent is 1g:10mL.

[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0027] 1. After modification by sol-gel method, the precursor-coated magnesium oxide particles can achieve high densification under normal pressure sintering conditions. This overcomes the limitations of pure magnesium oxide being difficult to densify under normal pressure sintering and requiring traditional aluminosilicate additives. It provides a densification basis for the application of materials in ultra-high temperature oxidizing atmospheres above 1600℃.

[0028] 2. After the precursor-coated titanium dioxide particles are modified by co-precipitation-thermal decomposition, they can be used as a functional additive to improve the volume resistivity of the material under ultra-high temperature oxidizing atmosphere above 1600℃ and improve the insulation resistance retention ability of the material after repeated thermal cycling, thus making up for the shortcomings of the system that relies solely on sintering aids to achieve densification in terms of ultra-high temperature insulation stability.

[0029] 3. This invention pre-coats two precursor particles through chemical condensation and then calcination, avoiding component segregation that is easily caused by physical mixing. This results in a more uniform distribution of functional additives in the grain boundary region. The material can still maintain a high volume resistivity in an ultra-high temperature oxidizing atmosphere above 1600℃, and the insulation resistance remains good after repeated thermal cycling. Combined with the high densification achieved by atmospheric pressure sintering of precursor-coated magnesium oxide particles, this invention solves the problem that it is difficult to achieve both atmospheric pressure densification and ultra-high temperature insulation stability in existing high-density magnesium oxide systems containing sintering aids. This meets the long-term service requirements of mineral-insulated cable equipment under extreme conditions such as aerospace and nuclear industry. Attached Figure Description

[0030] Figure 1 This is a physical image of the high-density magnesium oxide insulating material for ultra-high temperature applications according to the present invention. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1: This example discloses a high-density magnesium oxide insulating material for ultra-high temperature applications, comprising a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:1.2.

[0033] The precursor-coated magnesium oxide particles are obtained by coating the surface of magnesium oxide powder particles with a precursor gel layer using tetraethyl orthosilicate and tetrabutyl titanate as hydrolyzed precursors via a sol-gel method.

[0034] The precursor-coated titanium dioxide particles are obtained by loading a precursor coating layer onto the surface of anatase titanium dioxide nanoparticles using yttrium nitrate hexahydrate and stannous chloride as coating sources via a co-precipitation method.

[0035] The magnesium oxide powder has a purity of ≥99.9% and a particle size of 1~3μm; the anatase titanium dioxide nanoparticles have a purity of ≥99% and a particle size of ≤100nm.

[0036] The method for preparing the precursor-coated magnesium oxide particles includes the following steps:

[0037] M11. Under stirring, 10g of tetraethyl orthosilicate was dissolved in 50mL of anhydrous ethanol-water mixed solvent (anhydrous ethanol to water volume ratio 4:1), and 0.5mol / L nitric acid was added dropwise to adjust the pH to 3.5. The solution was pre-hydrolyzed in a 45℃ water bath for 2h to obtain the precursor sol. Separately, 3g of tetrabutyl titanate was dissolved in 12mL of anhydrous ethanol, and 0.9g of acetylacetone was added and stirred for chelation for 30min to obtain the precursor solution.

[0038] M12. Under stirring, the precursor solution was slowly added dropwise to the silicon precursor sol at a rate of 0.2 mL / min. After the addition was complete, stirring was continued for 2.5 h to obtain the composite precursor sol. 0.5 mol / L ammonia solution was added dropwise to the composite precursor sol to adjust the pH of the system to 7.0. Then, 80 g of high-purity magnesium oxide powder was added at 30 °C, ultrasonically dispersed for 15 min, and then stirred for another 1 h to obtain the reaction mixture.

[0039] M13. The reaction mixture was first vacuum dried at 45°C for 8 hours to remove most of the ethanol and water, and then heated to 90°C and vacuum dried to constant weight to obtain a dry powder. The dry powder was lightly ground and dispersed in an agate mortar and passed through a 100-mesh sieve to obtain precursor-coated magnesium oxide particles.

[0040] The method for preparing the precursor-coated titanium dioxide particles includes the following steps:

[0041] M21. Add 10g of anatase titanium dioxide nanoparticles to 100mL of deionized water and ultrasonically disperse for 30min to obtain a titanium dioxide suspension; dissolve 0.08g of yttrium nitrate hexahydrate in 20mL of deionized water to obtain a yttrium nitrate hexahydrate solution; separately dissolve 0.05g of stannous chloride (prepared immediately) in 5mL of deionized water and add 0.5mL of 1mol / L hydrochloric acid dropwise to inhibit hydrolysis and oxidation. Stir until completely dissolved and then mix with the yttrium nitrate hexahydrate solution to obtain a mixed solution.

[0042] M22. Under continuous stirring, the mixed solution is slowly added dropwise to the titanium dioxide suspension at a rate of 1-2 drops per second; after the addition is complete, stirring is continued for 30 minutes; then, 2 mol / L ammonia solution is added dropwise under stirring, and the dropping rate is controlled so that the pH of the system gradually rises to 9.5 within 12 minutes; stirring and aging are continued for 2-3 hours to obtain the suspension.

[0043] M23. Filter the suspension and wash it repeatedly with deionized water until the filtrate is neutral; dry the washed filter cake at 100℃ for 12h, lightly grind and disperse it in an agate mortar, and pass it through a 100-mesh sieve to obtain precursor-coated titanium dioxide particles.

[0044] The preparation method of the high-density magnesium oxide insulating material for ultra-high temperature applications includes the following steps:

[0045] M1. 80g of precursor-coated magnesium oxide particles and 0.96g of precursor-coated titanium dioxide particles were dispersed together in 810mL of ethanol-water mixed solvent (ethanol to water volume ratio 8:1). 0.1mol / L dilute hydrochloric acid was added dropwise to adjust the pH of the system to 5.0. The mixture was stirred in a 40℃ water bath for 3h to obtain a composite precursor slurry.

[0046] M2. The composite precursor slurry was vacuum dried at 60°C to constant weight to obtain a dry powder. The dry powder was lightly ground and dispersed in an agate mortar and passed through a 200-mesh sieve. The sieved powder was placed in a muffle furnace and heated to 680°C at a rate of 5°C / min under an oxidizing atmosphere, and held at that temperature for 2.5 hours. After cooling to room temperature in the furnace, the powder was removed, ground, and deagglomerated, and then passed through a 200-mesh sieve to obtain a high-density magnesium oxide insulating material for ultra-high temperature applications. A physical image of the high-density magnesium oxide insulating material for ultra-high temperature applications of this invention is shown below. Figure 1 As shown.

[0047] It should be noted that the ultra-high temperature high-density magnesium oxide insulating material is the raw material powder for downstream applications. This powder has been calcined, and the steps to make it into the final solid insulating product are as follows:

[0048] High-density magnesium oxide insulating material for ultra-high temperature applications is mixed with a molding binder, granulated, and then placed into a mold for dry pressing. The formed blank is then subjected to cold isostatic pressing at a pressure of 150–200 MPa for 2–5 minutes. The blank is then placed in a high-temperature atmosphere furnace and heated to 600–800°C at a rate of 1–3°C / min under flowing air, and held for 1–2 hours to remove the molding binder. After the binder removal is completed, the temperature is further increased at a rate of 3–5°C / min, and the green blank is sintered at atmospheric pressure under an oxidizing atmosphere at a sintering temperature of 1720–1780°C for 3–6 hours. After sintering, the blank is slowly cooled to 800°C at a rate of 3–5°C / min, and then cooled to room temperature with the furnace to obtain the finished product of high-density magnesium oxide insulating material for ultra-high temperature applications, either in bulk or tubular form.

[0049] Example 2: This example is based on Example 1, but differs from Example 1 in that it discloses a high-density magnesium oxide insulating material for ultra-high temperature applications, comprising a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:0.5.

[0050] The other components and preparation methods are the same as in Example 1.

[0051] Example 3: This example is based on Example 1, but differs from Example 1 in that it discloses a high-density magnesium oxide insulating material for ultra-high temperature applications, comprising a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:1.0.

[0052] The other components and preparation methods are the same as in Example 1.

[0053] Example 4: This example is based on Example 1, but differs from Example 1 in that it discloses a high-density magnesium oxide insulating material for ultra-high temperature applications. The material comprises a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination. The mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:1.5.

[0054] The other components and preparation methods are the same as in Example 1.

[0055] Example 5: This example is based on Example 1, but differs from Example 1 in that it discloses a high-density magnesium oxide insulating material for ultra-high temperature applications, comprising a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:2.0.

[0056] The other components and preparation methods are the same as in Example 1.

[0057] Comparative Example 1: This comparative example is based on Example 1, but differs from Example 1 in that the precursor-coated magnesium oxide particles in this comparative example are not modified with tetrabutyl titanate (i.e., only modified with tetraethyl orthosilicate).

[0058] The other components and preparation methods are the same as in Example 1.

[0059] Comparative Example 2: This comparative example is based on Example 1, but differs from Example 1 in that the precursor-coated magnesium oxide particles in this comparative example are not modified with tetraethyl orthosilicate (i.e., only modified with tetrabutyl titanate).

[0060] The other components and preparation methods are the same as in Example 1.

[0061] Comparative Example 3: This comparative example is based on Example 1, but differs from Example 1 in that the precursor-coated titanium dioxide particles in this comparative example are not modified with stannous chloride (i.e., only modified with yttrium nitrate hexahydrate).

[0062] The other components and preparation methods are the same as in Example 1.

[0063] Comparative Example 4: This comparative example is based on Example 1, but differs from Example 1 in that the precursor-coated titanium dioxide particles in this comparative example are not modified with yttrium nitrate hexahydrate (i.e., only modified with stannous chloride).

[0064] The other components and preparation methods are the same as in Example 1.

[0065] Comparative Example 5: This comparative example is based on Example 1, but differs from Example 1 in that unmodified magnesium oxide is used instead of precursor-coated magnesium oxide particles.

[0066] The other components and preparation methods are the same as in Example 1.

[0067] Comparative Example 6: This comparative example is based on Example 1, but differs from Example 1 in that unmodified titanium dioxide is used instead of precursor to coat titanium dioxide particles.

[0068] The other components and preparation methods are the same as in Example 1.

[0069] Comparative Example 7: This comparative example is based on Example 1, but differs from Example 1 in that unmodified magnesium oxide is used to replace the precursor coating magnesium oxide particles, and unmodified titanium dioxide is used to replace the precursor coating titanium dioxide particles.

[0070] The other components and preparation methods are the same as in Example 1.

[0071] Comparative Example 8: This comparative example is based on Example 1, but unlike Example 1, this comparative example does not add precursor-coated titanium dioxide particles.

[0072] The other components and preparation methods are the same as in Example 1.

[0073] Comparative Example 9: This comparative example differs from Example 1 in that the precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles are not chemically condensed together. Instead, anhydrous acetone is used as the dispersion medium (the ratio of the total mass of the precursor-coated magnesium oxide particles and the precursor-coated titanium dioxide particles to the volume of anhydrous acetone is 1 g: 2.0 mL), and high-purity magnesium oxide balls (MgO content ≥ 99.9%) are used as the grinding medium for ball milling (high-purity magnesium oxide...). The balls and the total mass of the powder were mixed at a ratio of 3:1. The ball milling speed was 200 r / min and the milling time was 6 h. After the ball milling was completed, the slurry was vacuum dried at 50-60℃ to constant weight. The dried powder was ground and passed through a 200-mesh sieve. The sieved powder was placed in a muffle furnace and heated to 680℃ at a rate of 5℃ / min under a flowing air atmosphere. The temperature was held for 2.5 h and then cooled to room temperature with the furnace. The powder was then removed, ground and deagglomerated, and passed through a 200-mesh sieve to obtain high-density magnesium oxide insulating material for ultra-high temperature applications.

[0074] The other components and preparation methods are the same as in Example 1.

[0075] Experimental verification:

[0076] Test specimen preparation:

[0077] (1) Granulation and dry pressing: Weigh 2.5g of high-density magnesium oxide insulating material for ultra-high temperature in Examples 1-5 and Comparative Examples 1-9, add 5wt% polyvinyl alcohol aqueous solution accounting for 2-3% of its mass as molding binder, mix evenly and granulate through an 80-mesh sieve, and dry at 60℃; put the granulated powder into a steel mold with an inner diameter of 20mm, and press it evenly to 200MPa on a manual tablet press at a loading rate of 10mm / min, hold the pressure for 2min, and demold to obtain a blank with a diameter of 20mm and a thickness of about 2.5-3mm.

[0078] (2) Cold isostatic pressing densification: After vacuum sealing the green billet with a rubber sleeve, it is placed in the cavity of a cold isostatic press and pressurized to 200 MPa at a rate of 50 MPa / min, held for 5 min, and then depressurized at a uniform speed. The billet is then removed, and the density and uniformity of the billet are further improved.

[0079] (3) Atmospheric pressure sintering: The cold isostatically pressed blank is placed flat in a corundum crucible and pushed into a high-temperature atmosphere furnace. Under a flowing air atmosphere (flow rate 200 mL / min), the temperature is increased to 600℃ at a rate of 3℃ / min for 1 hour to remove the binder, and then increased to 1720℃ at a rate of 5℃ / min and held for 3 hours. After the holding period, the temperature is slowly cooled to 800℃ at a rate of 3℃ / min, and then allowed to cool naturally to room temperature with the furnace. The resulting dense sintered magnesium oxide insulating material disc sample is obtained.

[0080] Experimental Verification 1: Bulk Density and Relative Density

[0081] The bulk density and relative compactness of sintered samples were determined using the Archimedes displacement method. The specific steps are as follows:

[0082] (1) Drying and weighing: The sintered and dense magnesium oxide insulating material disc sample was dried in an oven at 110℃ for 24 hours, and then placed in a desiccator to cool to room temperature. Its dry weight in air was measured using a high-precision analytical balance (sensitivity 0.1 mg) and recorded as m. 干 .

[0083] (2) Vacuum saturation: Immerse the dried sample in a beaker containing deionized water, place the beaker in a vacuum desiccator, evacuate to an absolute pressure of less than 2 kPa, and maintain for 30 min to ensure that the open pores are completely filled with water. Then restore to normal pressure and let stand for 10 min.

[0084] (3) Weighing the saturated wet weight: Take out the sample, quickly and gently wipe away the surface water with a wrung-out damp gauze, and immediately weigh the saturated sample in air using an analytical balance, and record it as m. 湿 .

[0085] (4) Weighing the buoyant weight: Suspend the above saturated sample in the basket below the balance, ensuring that the sample is completely immersed in deionized water and does not touch the container wall, and weigh its buoyant weight in the water, denoted as m. 水 .

[0086] (5) Calculate the bulk density:

[0087] ;

[0088] ;

[0089] In the formula, To test the density of deionized water at a given temperature, the density was determined by referring to a table based on the water temperature, with an accuracy of ±0.001 g / cm³. 3 ; The theoretical density of magnesium oxide insulating material is taken as 3.59 g / cm³. 3 .

[0090] Experimental Verification 2: Ultra-high Temperature DC Volume Resistivity

[0091] Both sides of the circular sample were lightly polished with 400-grit sandpaper and then cleaned and dried. On the measuring side, a circular measuring electrode with a diameter of 8 mm and a concentric annular protective electrode with an outer diameter of 18 mm and an inner diameter of 10 mm were screen-printed (with a 1 mm gap between the measuring electrode and the protective electrode). On the opposite side, a full-surface high-voltage electrode with a diameter of 19 mm was screen-printed. The electrode paste was a platinum-rhodium alloy paste (Pt-10Rh). After infrared drying for 30 min, the sample was heated to 900 °C at a rate of 3 °C / min and held for 15 min in a muffle furnace. It was then cooled with the furnace to obtain a sample coated with a porous platinum-rhodium electrode.

[0092] Three-electrode method (air atmosphere): The sample coated with a porous platinum electrode is mounted in a high-temperature resistivity testing fixture, ensuring good alignment and contact between the measuring electrode, protective electrode, and high-voltage electrode. Flowing air (100 mL / min) is introduced into the furnace, and the temperature is increased to the target temperature of 1650℃ at a rate of 5℃ / min, held for 30 min to ensure thermal equilibrium. An appropriate DC voltage is applied based on the estimated resistivity of the sample. >10 6 100V at Ω·cm, 10 5 ~10 6 10V at Ω·cm, <10 5 (1V or 0.1V at Ω·cm), polarize for 1h, and after the current stabilizes (the change range within 5 minutes is <2%), record the stable leakage current I and the actual applied voltage value.

[0093] The calculation formula is as follows (for calculating volume resistivity at 1650℃):

[0094] ;

[0095] In the formula, D is the thickness and A is the effective area of ​​the electrode.

[0096] Test Verification 3: Thermal Cycling Stability Test of Ultra-High Temperature Insulation Resistance

[0097] Repeated thermal cycling combined with DC resistance measurement (air atmosphere):

[0098] Following the method described in Experimental Verification 2, the temperature was initially raised to 1650℃ and the initial volume resistivity ρ was measured. v0 The temperature was lowered to 400℃ at a rate of 5℃ / min, then immediately raised back to 1650℃ at the same rate. After holding at this temperature for 30 minutes, the volume resistivity was measured again and recorded as ρ. v1 Repeat this "1650℃⇌400℃" cycle 10 times, recording ρ each time. vn The resistance retention rate after 10 cycles was calculated to evaluate the insulation performance stability of the sample under repeated medium-speed temperature changes. The lower limit temperature of the thermal cycle was set to 400℃, which corresponds to the minimum holding temperature of most high-temperature electric heating equipment under intermittent operation; the cooling rate of 5℃ / min simulated the medium-speed cooling condition in actual service.

[0099] ;

[0100] Table 1. Comparison of sintering densification properties:

[0101]

[0102] Table 2. Comparison of insulation performance and thermal cycling stability at ultra-high temperatures:

[0103]

[0104] Table 1 shows that the relative density of the sample coated with the precursor magnesium oxide particles is higher than that of the unmodified sample, confirming that sol-gel pre-coating is the key to achieving high densification during atmospheric pressure sintering. Table 2 shows that the sample with dual modified components exhibits better volume resistivity at ultra-high temperatures and better resistance retention after thermal cycling than the control sample lacking either modified component. Furthermore, comparing Example 1 and Comparative Example 9 reveals that chemical condensation composite primarily improves the resistance retention during thermal cycling compared to physical ball milling, with less impact on density and initial resistivity.

[0105] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high-density magnesium oxide insulating material for ultra-high temperature applications, characterized in that, The powder comprises a composite powder formed by chemical condensation reaction of precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles, followed by calcination; wherein the mass ratio of the precursor-coated magnesium oxide particles to the precursor-coated titanium dioxide particles is 100:0.5~2.

0. The precursor-coated magnesium oxide particles are obtained by coating the surface of magnesium oxide powder particles with a precursor gel layer using tetraethyl orthosilicate and tetrabutyl titanate as hydrolyzed precursors via a sol-gel method. The precursor-coated titanium dioxide particles are obtained by loading a precursor coating layer onto the surface of anatase titanium dioxide nanoparticles using yttrium nitrate hexahydrate and stannous chloride as coating sources via a co-precipitation method.

2. The high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 1, characterized in that, The magnesium oxide powder has a purity of ≥99.9% and a particle size of 1~3μm; the anatase titanium dioxide nanoparticles have a purity of ≥99% and a particle size of ≤100nm.

3. The high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 1, characterized in that, The method for preparing the precursor-coated magnesium oxide particles includes the following steps: M11. Under stirring, tetraethyl orthosilicate was dissolved in anhydrous ethanol-water mixed solvent, and dilute nitric acid was added dropwise to adjust the pH. Hydrolysis was then performed to obtain a precursor sol. Separately, tetrabutyl titanate was dissolved in anhydrous ethanol, and acetylacetone was added and stirred to obtain a precursor solution. M12. Add the precursor solution to the silicon precursor sol with stirring. Continue stirring after the addition is complete to obtain a composite precursor sol. Add dilute ammonia solution to the composite precursor sol to adjust the pH. Then add high-purity magnesium oxide powder, sonicate, and stir to react to obtain a reaction mixture. M13. Vacuum dry the reaction mixture to obtain a dry powder; grind and sieve the dry powder to obtain precursor-coated magnesium oxide particles.

4. The high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 3, characterized in that, The mass ratio of tetraethyl orthosilicate to tetrabutyl titanate is 1:0.2~0.4; the mass ratio of acetylacetone to tetrabutyl titanate is 1:3~1:4; and the mass ratio of high-purity magnesium oxide powder to the total mass of tetraethyl orthosilicate and tetrabutyl titanate is 5:1~10:

1.

5. The high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 1, characterized in that, The method for preparing the precursor-coated titanium dioxide particles includes the following steps: M21. Add anatase titanium dioxide nanoparticles to deionized water and sonicate to obtain a titanium dioxide suspension; dissolve yttrium nitrate hexahydrate in deionized water to obtain a yttrium nitrate hexahydrate solution; dissolve stannous chloride in deionized water and add 1 mol / L hydrochloric acid dropwise, stir and mix with the yttrium nitrate hexahydrate solution to obtain a mixed solution; M22. Add the mixed solution to the titanium dioxide suspension; after the addition is complete, stir the reaction; then add 2 mol / L ammonia solution to adjust the pH of the system; continue stirring and aging to obtain a suspension; M23. Filter the suspension and wash it with deionized water; dry the washed filter cake, grind it lightly and sieve it to obtain precursor-coated titanium dioxide particles.

6. The high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 5, characterized in that, The amount of yttrium nitrate hexahydrate added is 0.5-1% of the mass of anatase titanium dioxide nanoparticles; the amount of stannous chloride added is 0.3-0.8% of the mass of anatase titanium dioxide nanoparticles.

7. A method for preparing a high-density magnesium oxide insulating material for ultra-high temperatures, applied to the preparation of a high-density magnesium oxide insulating material for ultra-high temperatures as described in any one of claims 1 to 6, characterized in that, The method includes the following steps: M1. Precursor-coated magnesium oxide particles and precursor-coated titanium dioxide particles are co-dispersed in an ethanol-water mixed solvent, dilute hydrochloric acid is added dropwise to adjust the pH of the system, and the reaction is stirred to obtain a composite precursor slurry. M2. The composite precursor slurry is dried to obtain a dry powder; the dry powder is ground and sieved; the sieved powder is calcined in an oxidizing atmosphere; after cooling, it is taken out, ground, and sieved to obtain a high-density magnesium oxide insulating material for ultra-high temperature applications.

8. The method for preparing a high-density magnesium oxide insulating material for ultra-high temperature applications according to claim 7, characterized in that, The total mass ratio of the precursor-coated magnesium oxide particles and the precursor-coated titanium dioxide particles to the ethanol-water mixed solvent is 1g:10mL.

Citation Information

Patent Citations

  • Preparation method and application of high-temperature magnesium oxide powder additive and magnesium powder

    CN118724033A